Portuguese America under Foreign Threat and the Creation of the Concept of uti possidetis in the First half of the 18th Century - Ferreira Furtado, Junia (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2021)
The aim of this article is to discuss the relationship between invasions, cartography, and possessory law in the context of diplomatic relations between Portugal and Spain in the first half of the eighteenth century, in South America territories. The Castilian siege of Colônia do Sacramento and the French invasion of Fernando de Noronha island (1736 and 1737), awoke in the Portuguese ambassador D. Luís da Cunha the need to change the foundation on which the frontiers of Brazil were negotiated. He began to use the concept of uti possidetis as a strategy, which would become the directive for the diplomatic negotiations in the 1750 Treaty of Madrid. Despite its acceptance as a resource to demarcate frontiers, uti possidetis created various controversies at the moment of the demarcation of the territories and the Treaty was annulled by the Treaty of El Pardo (1761), when the legal frontiers returned to their previous positions.